One-carbon metabolic pathway is a novel molecular signature for CD44-positive intestinal-type gastric cancer - Seyeon Joo; Yoojin Bae; Bo Kyung Yoon; Yeonjin Je; Yuna Kim; Minki Kim; Su-Jin Shin; Sungsoon Fang; Jie-Hyun Kim (Cell Death Discovery)
Abstract Intratumoral heterogeneity (ITH), arising from various factors, plays a crucial role in diverse cancers, yet research on ITH remains in its early stages. To explore this phenomenon further, we conducted single-nuclei transcriptome profiling on patient-derived organoids (PDOs) from two histologically pure subtypes of gastric cancer. We identified differences in cancer stem cell marker expression among intestinal-type samples and their correlation with one-carbon (1C) metabolism. Notably, some gastric cancer samples, although histologically classified as intestinal-type, exhibited diffuse-like genetic characteristics. This finding suggests the potential for employing a 1C metabolism inhibition strategy as a therapeutic approach for these genetically diffuse-like gastric cancers. This study highlights the necessity of addressing ITH in PDO-based preclinical models and contributes valuable insights toward advancing precision medicine treatments for gastric cancer.